DAMPAK PANDEMI CORONA VIRUS DISEASE (COVID-19) TERHADAP PROSES PEMBELAJARAN DARING PADA MATA PELAJARAN AKUNTANSI DASAR DI SMK NEGERI 1 PURWASARI KARAWANG - Dicky Ramadhan Sudrajat (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2023)
The purpose of this research is to obtain information in the form of obstacles during the online teaching and learning process at home as a result of the global COVID-19 pandemic. The research used the exploratory case study method and the research approach used the qualitative case study method which was used to obtain information on the constraints and consequences of the COVID-19 pandemic on teaching and learning process activities at SMKN 1 Purwasari, Karawang Regency. Respondents for this study were teachers, students and parents of students at SMKN 1 Purwasari, Karawang Regency. The results of this study are that there are several obstacles experienced by students, teachers and parents in online teaching and learning activities.